Balancing Scales of Language Injustice - Rabow, Jerome; Dhillon, Manpreet (Scientific Research, 2015)
This paper addresses the ways in which our everyday usage of the common phrase “people of color” perpetuates a basic inequality in language use. A suggestion to eliminate inequality in teaching is proposed.
Keywords: Race; Racisim; Teaching; Inequality